2022
DOI: 10.1108/jiabr-03-2021-0095
|View full text |Cite
|
Sign up to set email alerts
|

Donors’ attitude towards fundraising efforts in UAE during COVID-19 pandemic: the moderating role of ethics

Abstract: Purpose This study aims to explore the antecedents of donors’ attitudes toward fundraising campaigns to fight COVID-19 in the United Arab Emirates (UAE) during the pandemic crisis. This manuscript identified how moderating effects of ethical dimensions can strengthen the relationship between trust in charity and charity projects with their attitude to raise funds to mitigate pandemic repercussions. Design/methodology/approach This study follows a quantitative approach by administering survey instruments to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…When we look at the studies examining the relationship between donation and religiosity, Reitsma et al (2006) concluded that there is a positive relationship between solid religious belief and intention to donate to charity. Sarea et al (2023) found a positive relationship between religious beliefs and attitudes towards donating to pandemic relief efforts. In addition, Abreu et al.…”
Section: Methodsmentioning
confidence: 99%
“…When we look at the studies examining the relationship between donation and religiosity, Reitsma et al (2006) concluded that there is a positive relationship between solid religious belief and intention to donate to charity. Sarea et al (2023) found a positive relationship between religious beliefs and attitudes towards donating to pandemic relief efforts. In addition, Abreu et al.…”
Section: Methodsmentioning
confidence: 99%
“…via web links, kiosks and physical booths located in shopping malls and residential areas. Therefore, COs' strategies should continue to evolve and provide up-to-date methods for such money transfers both online and offline which is similar to other Muslim countries (Sarea et al , 2022; Kasri and Yuniar, 2021). Second, as MN were also found to have a significant and positive relationship with behavioral intentions, we recommend that campaigns should continue to focus on people’s moral responsibility toward Islam.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…When referring to Muslim charities, there has been a decline in their income before COVID-19 because of mismanagement and scandals of charities (Gündoğdu, 2019). As a result of the mismanagement that has plagued Islamic donations, the trust of donors has declined (Abd Jalil et al , 2019) although authors identify trust as a highly essential charity activity in the United Arab Emirates (Sarea et al , 2022). Thus, there is a clear trend in which donors prefer to use their means when distributing charity because of mistrust of organizations (Kashif et al , 2018).…”
Section: Introductionmentioning
confidence: 99%